Virtual serious games for women’s health education: A scoping review - Krissy Jordan; Christine Kurtz Landy; Celina Da Silva; Mahdieh Dastjerdi; Bella Grunfeld (PLoS ONE, 2025)
Background Virtual serious games (VSGs) offer an engaging approach to women’s health education. This review examines the state of research on VSGs, focusing on intended users, design characteristics, and assessed outcomes. Methods Following JBI methodology guidance for the scoping review, searches were conducted in the MEDLINE, CINAHL, EMBASE, Web of Science, and PsycINFO databases from inception to April 22, 2024. Eligible sources included participants: women or females aged 18 years and older, with no restrictions based on health condition or treatment status; concept: VSGs; context: settings where health education is provided. Sources were restricted to English language and peer-reviewed articles. Two reviewers independently screened titles, abstracts, and full texts using eligibility criteria. Data extraction was performed by one reviewer and verified by another using a custom tool. Quantitative (e.g., frequency counting) and qualitative (content analysis) methods were employed. The findings were organized into figures and tables accompanied by a narrative description. Results 12 studies from 2008 to 2023, mostly in the U.S. (66.7%), explored various age groups and women’s health, focusing on breast and gynecological cancer (67%). Half (50%) of the VSGs were theory-informed; 41.7% involved users, and 58.3% had partnerships. Game types included tablet (41.7%), mobile (25%), and web (33.3%). Gameplay dosage varied from single session (50%) to self-directed (25%) and specific frequency (25%). Gameplay duration was self-directed (50%) or fixed lengths (50%). Outcomes included knowledge (50%), skills (16.7%), satisfaction (58.3%), health-related metrics (41.7%), and gameplay analysis (16.7%). Conclusions Studies show increased interest in VSGs for women’s health education, especially regarding breast and gynecological cancer. The focus on theoretical frameworks, user involvement, and collaborations highlights a multidisciplinary approach. Varied game modalities, dosage, and assessed outcomes underscore VSG adaptability. Future research should explore long-term effects of VSGs to advance women’s health education.